2022
DOI: 10.3389/fpsyg.2022.1041376
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and adolescent mental health in China: Micro evidence and socioeconomic mechanisms

Abstract: Although the impact of the COVID-19 pandemic on adolescent mental health has received sufficient attention in the medical and public health fields, analysis from the social science perspective is still lacking. By regarding the shock of COVID-19 pandemic as a quasi-natural experiment, this study adopts the Difference-in-Differences (DID) model and large microdata from Shandong Province, China, to identify the causal effect of the COVID-19 pandemic on the mental health of senior high school students. We find th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…The COVID-19 pandemic has adverse mental health consequences among Chinese K-12 students, including depressive symptoms, emotional symptoms, stress symptoms, anxiety, inattention, peer relationship problems, and posttraumatic stress disorders (PTSD). [55][56][57][58] These mental health problems can affect a K-12 student's energy level, concentration, optimism, mental capability, and dependability, which can hinder his or her academic performance. 59 We found that students with high household incomes, students with higher intelligence quotients, and students who read books are more likely to have good academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has adverse mental health consequences among Chinese K-12 students, including depressive symptoms, emotional symptoms, stress symptoms, anxiety, inattention, peer relationship problems, and posttraumatic stress disorders (PTSD). [55][56][57][58] These mental health problems can affect a K-12 student's energy level, concentration, optimism, mental capability, and dependability, which can hinder his or her academic performance. 59 We found that students with high household incomes, students with higher intelligence quotients, and students who read books are more likely to have good academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first infected case was reported in December 2019, China has implemented strict lockdown measures such as the “zero-COVID” policy through extensive testing, contact tracing, and quarantine apparatus (Normile, 2021 ; Wang et al, 2021 ). Several studies have found that the pandemic elevated the level of stress and anxiety across different age cohorts in China (Hu et al, 2021 ; Chen B. et al, 2022 ; Yang et al, 2022 ). On the other hand, although China had the lowest GDP growth rate 1 (2.2%) and the highest unemployment rate 2 (4.2%) in 2020 in the last decade, it was one of the very few countries having positive GDP growth during the pandemic (World-Bank, 2022 ).…”
Section: Introductionmentioning
confidence: 99%